Liver iron overload within a UK based population by sex - Mckay, A; Wilman, H; Kelly, M; Kin, S; Phillips, M; Jandor, A; Bell, J; Thomas, L; Milanesi, M; Neubauer, S; Banerjee, R (Elsevier, 2017)
Estimates of iron-overload, the most common cause of which is haemochromatosis, have been lacking within the UK population. As iron overload is treatable with venesection and/or chelation, early identification has clear utility. Long term consequences of untreated hepatic iron overload/haemochromatosis include cirrhosis, hepatocellular cancer and heart failure. To define the epidemiology of iron overload, we studied 5353 volunteers between the ages of 40 and 73 (Mean = 61 years) as part of the UK Biobank project.